Hybrid laser-assisted forming process for ultralight three-dimensional glass elements - Hassel Robin (EDP Sciences, 2021)
As part of a research project, a new hybrid forming process for ultrathin three-dimensional glass elements was developed. In a continuous process chain, the three-part procedure enables large-area gravity-assisted bending of thin glass, partial deep-drawing of individual small structures using CO2 laser radiation and cutting of flexible inner and outer contours. Using an experimental setup with a laser scanning system, novel component designs can be generated in a highly flexible and reproducible manner. This can open up new application fields or expand existing ones, for example in the area of cover glasses for display technology.